Edges in syntax : scrambling and cyclic linearization - Ko, Heejeong (Oxford studies in theoretical linguistics., 2014)
This text examines how word order variations in language can be regulated by various factors in cyclic syntax. In particular, it offers a valuable contribution to the current debate concerning the effect of cyclic Spell-out on the (re- )ordering of elements in scrambling. Heejeong Ko provides in-depth discussion of the interaction of the syntax-phonology interface with operations at the syntax proper, as well as examining how the semantic meaning of a structure can be correlated with certain types of orderings in cyclic edges of the syntax.